A guide to global access to HPV vaccination to all women in low- and middle-income countries; a minireview of innovation and equity - Ewongwo, Agnes; Sahor, Aji Fatou; Ngwa, Wilfred; Nwachukwu, Chika (Frontiers in Oncology, 2024)
IntroductionCervical cancer is caused by the human papillomavirus (HV), and accounts for more than 311,000 preventable deaths annually, with 85% occurring in low-and middle-income countries. Despite being preventable through screening and screening, significant barriers to implementing HPV vaccination persist in developing nations. This review study aims to identify these barriers and propose innovative, evidence-based solutions to improve vaccination rates and reduce cervical cancer mortality.MethodsA systematic review search was conducted using PubMed, Embase, and Cochrane Database of Systemic Reviews. Keywords related to HPV vaccination barriers and implementation strategies in developing countries were used. Relevant demonstration projects, pilot studies, and evidence-based research articles were reviewed.ResultsIdentifiable barriers to a successful vaccine implementation program in a developing country include vaccine costs, societal, cultural resistance, misinformation, logistical challenges in vaccine delivery, and inadequate human resources. Solutions to these barriers include a subsidized vaccine pricing, community sensitization, education and well-trained media professionals to dispel misinformation, and partnerships with both public and private sector for efficient vaccine distribution.DiscussionThese findings highlight critical barriers that impede HPV vaccination efforts in developing countries and offers practical solutions to overcome these challenges. This aggregate of data can help inform future developing countries’ implementation programs to further the World Health Assembly mission to vaccinate 90% of eligible girls globally by 2030.